Improved motor function in a pre-ambulatory child with spastic bilateral cerebral palsy, using a custom rigid ankle-foot orthosis–footwear combination: A case report. (August 2019) - Young, Joshua; Jackson, Sally
Background: Ankle-foot orthoses may be used in pre-ambulatory children with cerebral palsy; however, their effect on the acquisition of walking is unknown. This case report aims to evaluate the effect of an ankle-foot orthosis–footwear combination on the acquisition of walking in a single subject with cerebral palsy. Case Description and Methods: This study reports the orthotic management of a single child with spastic bilateral cerebral palsy over a 15-month period, during which time the ability to independently stand and walk was acquired. Custom rigid ankle-foot orthoses were prescribed. Gait speed and Edinburgh Visual Gait Score were assessed with and without the orthoses. Findings and Outcomes: The subject developed the ability to stand and walk using an ankle-foot orthosis–footwear combination with a walker frame, and to a limited extent without a walker frame. The subject remained unable to take independent steps unless wearing the ankle-foot orthosis–footwear combination. Clinically significant differences in gait speed and Edinburgh Visual Gait Score were observed. Conclusion: An ankle-foot orthosis–footwear combination may aid the development of independent walking in some children with cerebral palsy. Further research on the effects of orthoses on the acquisition of walking ability in children with cerebral palsy is needed. Clinical relevance: Custom rigid ankle-foot orthoses combined with footwear may aid the development of independent standing and walking in some children with bilateral spastic cerebral palsy. This intervention may be considered in clinical practice and future research in this patient group.